2016
DOI: 10.1515/gps-2016-0032
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted preparation of almond shell-based activated carbon for methylene blue adsorption

Abstract: This study reports the synthesis of a novel adsorbent, hereinafter named almond shell-based activated carbon (ASAC), from waste almond shells (AS) via exposure to microwave radiation and the use of ZnCl 2 as a chemical activator. Synthetic conditions were further elaborated using the response surface methodology to optimize the adsorption capacity of ASAC for methylene blue (MB) dye. The optimized ASAC preparation conditions were found to be as follows: a mass (ZnCl 2 /AS) ratio of 3:1 (w/w) and microwave heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 35 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…Ramesh et al (2015) studied the hydrogen adsorption behavior of activated carbons derived from tamarind seeds and found that the hydrogen storage capacity of activated carbon with a 1785 m 2 /g surface area was 4.73 wt % at room temperature and 40 bar . Activated carbons were produced from almond shells by physical and chemical activation methods. Izgi et al (2019) prepared activated carbon by microwave irradiation from almond shells and determined that the maximal surface area was 1128 m 2 /g; and Du et al (2016) studied the synthesis of a novel adsorbent from waste almond shells (AS) and found that the optimized activated carbon preparation conditions were to be as follows: a mass (ZnCl 2 /AS) ratio of 3:1 (w/w) and microwave heating time period of 15 min at 900 W . As can be seen from the above studies, there is no study on the production of activated carbon from almond shells by the microwave irradiation method to store hydrogen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ramesh et al (2015) studied the hydrogen adsorption behavior of activated carbons derived from tamarind seeds and found that the hydrogen storage capacity of activated carbon with a 1785 m 2 /g surface area was 4.73 wt % at room temperature and 40 bar . Activated carbons were produced from almond shells by physical and chemical activation methods. Izgi et al (2019) prepared activated carbon by microwave irradiation from almond shells and determined that the maximal surface area was 1128 m 2 /g; and Du et al (2016) studied the synthesis of a novel adsorbent from waste almond shells (AS) and found that the optimized activated carbon preparation conditions were to be as follows: a mass (ZnCl 2 /AS) ratio of 3:1 (w/w) and microwave heating time period of 15 min at 900 W . As can be seen from the above studies, there is no study on the production of activated carbon from almond shells by the microwave irradiation method to store hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…30 Activated carbons were produced from almond shells by physical and chemical activation methods. 31−33 Izgi et al (2019) prepared activated carbon by microwave irradiation from almond shells and determined that the maximal surface area was 1128 m 2 / g; 34 and Du et al (2016) studied the synthesis of a novel adsorbent from waste almond shells (AS) and found that the optimized activated carbon preparation conditions were to be as follows: a mass (ZnCl 2 /AS) ratio of 3:1 (w/w) and microwave heating time period of 15 min at 900 W. 35 As can be seen from the above studies, there is no study on the production of activated carbon from almond shells by the microwave irradiation method to store hydrogen. Furthermore, almond shells are an agricultural waste like biomasses used in the production of some other activated carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its short duration, homogeneity, selective and fast process, energy saving and simple operation, microwave-assisted carbonization has drawn increasing attentions. [88,121] The main difference between microwave-assisted and conventional heating methods is the way to generate heat. The heating rate of conventional carbonization is relatively low, and the heat is transferred from the surface to the interior, so the adsorption capacity of active carbon obtained is not ideal.…”
Section: Microwave-assisted Carbonizationmentioning
confidence: 99%
“…40,41 The increase of negative charge on adsorbent surface enhances the electrostatic attraction of naphthalene, thus increasing the adsorption capacity of HMAC and HC to naphthalene. 42…”
Section: Effect Of Ph On Adsorption Capacity Of Naphthalene On Hc Andmentioning
confidence: 99%